KEBUDAYAAN PONOROGO DALAM KARTU KUARTET DAN BUKU CERITA BERGAMBAR - Chandra, Nurrul; Candrasari, MC. Wara (Program Studi Pendidikan Seni Rupa FBS UNJ, 2024)
This study aims to introduce the uniqueness of Reog Ponorogo in a concise and easily understandable manner as a cultural learning tool. It employs engaging storytelling tailored for children aged 12–15 through an illustrated storybook and quartet cards. The research adopts a qualitative methodology with a research-led practice approach. The illustrated storybook and Ponorogo cultural quartet cards for adolescents are visualized using a simplified cartoon style with distortion techniques. Output of the research yields an illustrated storybook titled